Air-Sea Interaction in Biophysical Modeling: With focus on Northeast Arctic Cod - Strand, Kjersti Opstad (The University of Bergen, 2019)
The focus of this thesis is on upper ocean dynamics and the interactions between the atmosphere and the oceans in relation to early life stages of Northeast Arctic cod. The main spawning sites of Northeast Arctic cod are along the Norwegian coast with positively buoyant eggs being transported towards the nursery grounds of the Barents Sea by the prevailing ocean currents. The physical processes investigated are the role of the wind-driven transport, cross-shelf exchange, vertical current shear, stratification and mixing processes affecting dispersal of the early life stages of cod. The first main finding is a modeled potential connectivity route of Northeast Arctic cod due to wind-driven transport and cross-shelf exchange towards the Northeast Greenland shelf. This modeled transport route is supported by observations of cod at the Northeast Greenland shelf as well as a surface drifter trajectory. Northeasterly winds over several days during spring cause higher occurrences of cross-shelf transport of cod, while southwesterly winds are maintaining the prevailing path towards the Barents Sea. The spawning ground close to the Norwegian continental shelf edge has the highest probability for cross-shelf transport. The second main finding is the role of vertical current shear causing deviations in vertical cod egg concentrations from the diffusion-buoyancy equation within a limited spawning ground. Since cod eggs are positively buoyant, the concentrations are expected to increase towards the surface. By investigating the occasionally observed sub-surface maxima in NEA cod egg concentrations the importance of variable current forcing in the vertical and spatially limited spawning grounds are identified as necessary conditions. The third main finding is the importance of correct representation of ocean stratification. A shallow surface layer will be more dynamically responsive to wind forcing, and effort should be made to ensure correct representation of stratification in physical-biological modeling. Here, this is ...